Social Studies Learning Disciplinary Strategies in Elementary Schools - Hasrudin Nur; Suciyati Suciyati; Hardiansyah Hardiansyah (Yayasan Insan Mulia Bima, 2024)
The purpose of writing this article is to understand the description of social studies learning discipline and strategies for creating social studies learning discipline in the school environment. The method used in this research is descriptive qualitative. Data was collected through interviews, observations and conclusions. Meanwhile, data analysis is carried out by reduction, interpretation and drawing conclusions. The research results show that in implementing social studies discipline learning strategies at SDN 1 Tonroge Sidrap, what is effective is not only about providing knowledge, but also creating learning experiences that are motivating and relevant for children. With a creative and engaging approach, we can help form a solid foundation for students' understanding and interest in Social Sciences